Molecular Structure, Vibrational Studies and Reactivity Descriptors Analysis of 4-[2-(tert-butylamino)-1-hydroxyethyl]-2-(hydroxymethyl)Phenol - Gangadharan, Rubarani P. (Trends in Sciences, 2022)
The compound 4-[2-(tert-butylamino)-1-hydroxyethyl]-2-hydroxymethyl)phenol (4BAHEHMP)was chosen for investigation and characterized by FT- IR and FT- Raman spectral analysis. The compound has been studied significantly by using density functional theory (DFT) calculations by the B3LYP method at the 6-31++G(d,p) basis set level. The calculated results show that the structural parameters can be reproduced well with the predicted geometry. The experimental vibrational frequencies were compared with the scaled vibrational frequencies for the assignment of vibrational bands. In addition to the DFT calculations of the compound, the calculations were performed for Fukui functions to explain the chemical selectivity or reactivity sites such as the molecule's nucleophilic, electrophilic, and radical attack in the compound. Mulliken atomic charges are calculated for the determination of electronic charge distribution and reactive sites which proves the formation of intermolecular interaction in solid forms provided by the significant region of electronegativity around oxygen atoms and the net positive on hydrogen and nitrogen atoms.The chemical and thermal stability of the compound is studied by using DFT method for different temperatures and it shows that thermodynamic parameters increase with increase in temperature. HIGHLIGHTS Vibrational spectra (FT-IR and FT-Raman) of the title molecule were analysed with DFT supported computational technique Reactive regions of the title compound were reported using MEP and Fukui function studies The chemical and thermal stability of the compound was computed by using DFT method for various temperatures and it shows that thermodynamic parameters increase with increase in temperature GRAPHICAL ABSTRACT